Natural D‐glucose as a biodegradable MRI relaxation agent. Issue 3 (27th June 2014) - Yadav, Nirbhay N.; Xu, Jiadi; Bar‐Shir, Amnon; Qin, Qin; Chan, Kannie W.Y.; Grgac, Ksenija; Li, Wenbo; McMahon, Michael T.; van Zijl, Peter C.M.
<x xml:space="preserve">Abstract</x> Purpose Demonstrate applicability of natural D‐glucose as a T2 MRI contrast agent. Methods D‐glucose solutions were prepared at multiple concentrations and variable pH. The relaxation rate (R2 = 1/T2) was measured at 3, 7, and 11.7 T. Additional experiments were performed on blood at 11.7 T. Also, a mouse was infused with D‐glucose (3.0 mmol/kg) and dynamic T2 weighted images of the abdomen acquired. Results The transverse relaxation rate depended strongly on glucose concentration and solution pH. A maximum change in R2 was observed around physiological pH (pH 6.8‐7.8). The transverse relaxivities at 22°C (pH 7.3) were 0.021, 0.060, and 0.077 s−1mM−1 at 3.0, 7.0, and 11.7 T, respectively. These values showed good agreement with expected values from the Swift‐Connick equation. There was no significant dependence on glucose concentration or pH for T1 and the diffusion coefficient for these solutions. The transverse relaxivity in blood at 11.7 T was 0.09 s−1mM−1. The dynamic in vivo experiment showed a 10% drop in signal intensity after glucose infusion followed by recovery of the signal intensity after about 50–100 s. Conclusion Glucose can be used as a T2 contrast agent for MRI at concentrations that are already approved for human use. Magn Reson Med 72:823–828, 2014. © 2014 Wiley Periodicals, Inc.